Effect of hot environmental conditions on physical activity patterns and temperature response of football players - Özgünen, K. T.; Kurdak, S. S.; Maughan, R. J.; Zeren, C.; Korkmaz, S.; Yazici, Z.; Ersöz, G.; Shirreffs, S. M.; Binnet, M. S.; Dvorak, J. (Scandinavian Journal of Medicine & Science in Sports, 2010)
Heat stress may contribute to decreased match performance when football is played in extreme heat. This study evaluated activity patterns and thermal responses of players during soccer matches played in different environmental conditions. Non-acclimatized soccer players (n=11, 20±2 years) played two matches in conditions of moderate heat (MH) and high heat (HH) index. Core temperature (Tc) and physical performance were measured using a telemetric sensor and a global positioning system, respectively. The average ambient temperature and relative humidity were MH 34±1 °C and 38±2%; HH 36±0 °C and 61±1%. Peak Tc in the MH match was 39.1±0.4 °C and in the HH match it was 39.6±0.3 °C. The total distance covered in the first and second halves was 4386±367 and 4227±292 m for the MH match and 4301±487 and 3761±358 m for the HH match. Players covered more distance (P<0.001) in the first half of the HH match than in the second half. In football matches played at high environmental temperature and humidity, the physical performance of the players may decrease due to high thermal stress.